Key factors contributing to postgraduate students’ success: Making a case for Coronavirus-19 and beyond - Sosibo, L. (South African Journal of Higher Education, 2024)
Coronavirus-19 (COVID-19) pandemic caused major disruptions to the education sector, with detrimental effects on the supervision of postgraduate students and their success. Higher education institutions (HEIs) shut down to observe COVID-19 protocols and minimise the spread of the virus. University closures forced postgraduate-supervision processes to be conducted online, resulting in students experiencing many challenges, such as, loss of social networks and social interaction, lack of access to university computer laboratories and software, inability to collect face-to-face data, and wellness and mental problems. Whereas abundant research exists on COVID-19, little is known about factors that contributed to postgraduate students’ success during the COVID-19 pandemic. This qualitative case study reports on the factors that promoted student success during the COVID-19 pandemic, from the perspective of 23 postgraduate students. Data were collected through an online questionnaire and analysed through colour-coding and thematic categorisation. Results revealed that both students and supervisors contributed to the success of postgraduate students. They also showed that some students possessed certain attributes that enhanced their success, as well as that some postgraduate supervisors employed novel approaches to students’ supervision that promoted students’ success. This article encourages HEIs to leverage these factors to promote postgraduate student success beyond the COVID-19 pandemic.